The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1101/lm.598307
|View full text |Cite
|
Sign up to set email alerts
|

Temporal requirement of C/EBPβ in the amygdala following reactivation but not acquisition of inhibitory avoidance

Abstract: Following learning, a memory is fragile and undergoes a protein synthesis-dependent consolidation process in order to become stable. Established memories can again become transiently sensitive to disruption if reactivated and require another protein synthesis-dependent process, known as reconsolidation, in order to persist. Here, we show that, in the basolateral amygdala (BLA), protein synthesis is necessary for both consolidation and reconsolidation of inhibitory avoidance (IA) memory, while the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 87 publications
6
80
0
Order By: Relevance
“…These findings are consistent with those of many prior studies involving injections of protein synthesis inhibitors into the hippocampus (e.g., Bourtchouladze et al 1998;Quevedo et al 1999Quevedo et al , 2004Taubenfeld et al 2001;Barriantos et al 2002;Agnihotri et al 2004;Artinian et al 2007), as well as into other brain areas such as the amygdala (Nader et al 2000;Schafe and LeDoux 2000;Debiec et al 2002;Duvarci et al 2005;Parsons et al 2006;Milekic et al 2007), and prefrontal cortex (Santini et al 2004;Akirav and Maroun 2006;Touzani et al 2007). These reports are part of a large set of papers showing that direct brain injections of protein synthesis inhibitors produce amnesia for many tasks (cf.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with those of many prior studies involving injections of protein synthesis inhibitors into the hippocampus (e.g., Bourtchouladze et al 1998;Quevedo et al 1999Quevedo et al , 2004Taubenfeld et al 2001;Barriantos et al 2002;Agnihotri et al 2004;Artinian et al 2007), as well as into other brain areas such as the amygdala (Nader et al 2000;Schafe and LeDoux 2000;Debiec et al 2002;Duvarci et al 2005;Parsons et al 2006;Milekic et al 2007), and prefrontal cortex (Santini et al 2004;Akirav and Maroun 2006;Touzani et al 2007). These reports are part of a large set of papers showing that direct brain injections of protein synthesis inhibitors produce amnesia for many tasks (cf.…”
Section: Discussionsupporting
confidence: 82%
“…Although the use of ODNs has proven successful in the hippocampus (Guzowski and McGaugh, 1997;Guzowski et al, 2000;Taubenfeld et al, 2001), fewer studies have used ODNs to manipulate gene expression in the amygdala (but see Malkani et al, 2004;Milekic et al, 2007). In our experiments, we show that intra-LA infusion of a biotinylated Arc/Arg3.1 ODN exhibits significant spread within the LA.…”
Section: Discussionmentioning
confidence: 50%
“…Toward this end, we used the same behavioral protocol that previously showed that IA reconsolidation is disrupted by post-retrieval administration of the protein synthesis inhibitors anisomycin and cycloheximide (Milekic and Alberini 2002;Milekic et al 2007) as well as of the antagonist of glucocorticoid receptors RU38486 (Taubenfeld et al 2008). Groups of rats were trained with 0.9 mA footshock intensity and tested 48 h later (Test 1).…”
Section: Resultsmentioning
confidence: 99%
“…The IA was performed as previously described (Milekic et al 2007). Briefly, the IA box (Model ENV-010MC, Med Associates) consisted of a lit (safe) compartment and a dark (shock) compartment separated by a door.…”
Section: Inhibitory Avoidance (Ia)mentioning
confidence: 99%